From west to east: Heterogeneity in the life history traits of a small pelagic fish (Sardina pilchardus) throughout the Mediterranean - Caballero-Huertas, Marta; Frigola-Tepe, Xènia; Viñas, Jordi; Muñoz, Marta (Frontiers in Marine Science, 2023)
Small pelagic fish are key elements of marine trophic networks and are of great importance to the total landing of marine species. Over the last decades, a decrease in biomass and catches of European sardine has been described, especially in the Mediterranean Sea, as an indication of a drop in stock condition. Multiple causes, including direct and indirect anthropogenic factors, seem to affect this ecologically and economically important species. To address this issue, it is important to identify the current variability in sardine status and understand the strategies for energy allocation, which are intimately related to reproductive potential and recruitment. We analyzed the somatic condition through tissue and mesenteric lipid measurements, relative condition (Kn) and hepatosomatic (HSI) indices, and reproductive condition with the gonadosomatic index (GSI) in four subareas of the Mediterranean (Northern Alboran, Northern Spain, the Northern Adriatic, and the Aegean Sea) and an outgroup from the Atlantic. The analyses were performed within the gonadal development cycle since translocation to reproduction may mask the state of actual energy reserves for comparison. The results revealed marked differences in health status among subareas, highlighting the low condition of Northern Spain sardines throughout the annual cycle. The uniform condition throughout gonadal development in the Northern Adriatic suggests that resource availability modulates the reproductive strategy since in this locality, sardines would have high dependence on immediate reserves, not behaving as strict capital breeders. Moreover, similarities between Alboran and Atlantic stocks are discussed, highlighting the marked energy replenishment of the latter after reproduction compared to the Mediterranean stocks. The Aegean stock was the fastest to reach its maximum after spawning, presenting low condition values from the developing to actively spawning period, but with the greatest recovery at the regressing phase, coinciding with a peak in productivity. Finally, the role of the liver in sardine energy storage is analyzed considering stock heterogeneity, potentially indicating that HSI is intimately related to feeding activity. Given the divergences among stocks, we propose concrete measures for managing this resource (i.e., the need for adapting the close seasons), which could be applied to other species in similar contexts.